A = 6
tn = a + (n - 1)d
t4 = 6 + 3d = 12
3d = 12 - 6 = 6
d = 6/3 = 2
f(n + 1) = f(n) + 2
Answer: 25
Step-by-step explanation:
look at the question
Divide by 365 then by 24 then by 60 and then by 60 again :)
Answer:
9 1/3
Step-by-step explanation:
Make 2/3 , 1/2 , & 1/6 have the same denominator. 6 is the least common multiple for all 3 fractions.
2/3 gets multiplied by 2/2
1/2 gets multiplied by 3/3
1/6 stays the same
2/3 becomes 4/6
1/2 becomes 3/6
1/6 stays 1/6
Follow the order of operations from the original equation.
4/6 - 3/6 = 1/6 then 1/6 + 1/6 = 2/6
6 - 1 = 5 then 5 + 4 = 9
Simplify 2/6 to 1/3
Remember to add 1/3 back to 9 making it 9 1/3
Answer:
A
Step-by-step explanation: